2008
DOI: 10.2527/jas.2007-0507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carcass characteristics of Bos indicus and tropically adapted Bos taurus breeds selected for postweaning weight

Abstract: Data from 9 studies were compiled to evaluate the effects of 20 yr of selection for postweaning weight (PWW) on carcass characteristics and meat quality in experimental herds of control Nellore (NeC) and selected Nellore (NeS), Caracu (CaS), Guzerah (GuS), and Gir (GiS) breeds. These studies were conducted with animals from a genetic selection program at the Experimental Station of Sertãozinho, São Paulo State, Brazil. After the performance test (168 d postweaning), bulls (n = 490) from the calf crops born bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
4
22
1
4
Order By: Relevance
“…Shear force at 14 and 21 days of postmortem aging (Table 1) is similar to that described by Bonilha et al (2008), which found 4.56 and 4.53 for selected and non-selected Nellore, respectively. It is important to note that there is large variance for this trait in Nellore cattle.…”
Section: Descriptive Analysissupporting
confidence: 71%
“…Shear force at 14 and 21 days of postmortem aging (Table 1) is similar to that described by Bonilha et al (2008), which found 4.56 and 4.53 for selected and non-selected Nellore, respectively. It is important to note that there is large variance for this trait in Nellore cattle.…”
Section: Descriptive Analysissupporting
confidence: 71%
“…Zootec., 46(5): [393][394][395][396][397][398][399]2017 in purebreds (Chase et al, 2000;Bonilla et al, 2007;Coleman et al, 2012;Sollecito et al, 2016). However, there is a lack of studies and information regarding the use of local breeds in industrial crosses, with the exception of Caracu breed that has already been evaluated in several production systems and diverse environments and is already part of Brazilian agribusiness (Bonilha et al, 2007;Moreira et al, 2016). Thus, this research aimed to evaluate the use of Curraleiro Pé-Duro (CPD) bulls in crossbreeding with Nellore (NEL) cows to increase meat production on natural pastures of Piauí State, Brazil, and to give use to this breed in risk of extinction.…”
Section: Introductionmentioning
confidence: 99%
“…The average weight of an animal of the Nellore breed typical in the Amazon is 425kg, and carcass weight is approximately 246 kg [59]. The average export value of this meat, as fresh or frozen beef, was USD 4.06/kg in 2010 [60], making the average value of the beef in one head of cattle USD 999.…”
Section: Cattle Products and Valuesmentioning
confidence: 99%